A Conceptual Metaphor-based Approach to Understanding English and Arabic Idioms of Emotions - Mjilla, Rachid; Hassane Darir, Hassane Darir (International Journal of Language and Literary Studies, 2025)
The present study investigates the conceptual metaphor-based approach to idiomatic expressions of emotions in English and Arabic. Through examining idioms related to emotions such as anger, happiness, and sadness, the study explores metaphorical language structures within each language, as well as how these metaphors affect bilingual learners. The study also explores the impact of L1 (native language) transfer on idiom interpretation in the TL (target language). For these reasons, we conducted a mixed approach addressing 42 correspondents. The results show that when idioms are presented within a framework based on their underlying conceptual metaphors, they can be better understood and remembered than without any conceptual framework context. The study also explores how cultural context influences idioms of emotions and how being conscious of conceptual metaphors can help in second-language learning. Among the four categories of idioms studied, the highest success rate is Shared Metaphorical Concepts at 86.2%, indicating that a universal or general metaphor across languages greatly helps L2 learners in understanding and interpreting. The lowest score is English Idioms with No Arabic Equivalent Metaphors at 57.1%, which suggests that metaphor remains the main challenge for learners. In addition, the findings show that the conceptual metaphor-based approach is a more effective pedagogical method for teaching idioms in EFL contexts, since it increases one's awareness of idioms and bridges the linguistic and cultural gap between English and Arabic. <!--a=1--><!--a=1-->